If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2x = 2 Reorder the terms: 2x + y = 2 Solving 2x + y = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 2x + y + -1y = 2 + -1y Combine like terms: y + -1y = 0 2x + 0 = 2 + -1y 2x = 2 + -1y Divide each side by '2'. x = 1 + -0.5y Simplifying x = 1 + -0.5y
| -3*10= | | 9x+4=14x-3 | | -5(3x+4)=10 | | -7x-2=10 | | 2.5x+2.79=10.21 | | 7(x)+5=6(x) | | x-4/3=11/12+3/4x | | 3w+2(2w-6)+8=3 | | y=(100)/(2+9e^3x) | | 4(2v-4)-3v=4 | | -6/5x=8 | | 7/3+10/3y=3y-2 | | 1/2+x=5/4 | | -0.1x+6.52=-0.5x+1.72 | | x-3/4=11/12+3/4x | | 6x^2-11x-5=0 | | 2(x+8)/3 | | 35z^2-44z-7=0 | | 7(5-8)+[6+4(8-9)]=x | | 2x+-8=3x+5 | | 18x^2-x+75=0 | | 6a-9a= | | (63-9x)/(x+3) | | F+6=-8 | | 3(x)-4=x(5) | | 2.2+0.4x=0.6 | | 12x^2y-18x^2-18y+27= | | 4x^2-1-8x=0 | | 16u-6u=20 | | -3x^2+24x+144=0 | | 3(4u+2)=-30 | | 4x-6=2x-9 |